2022
DOI: 10.3389/fmicb.2022.820920
|View full text |Cite
|
Sign up to set email alerts
|

Co-selective Pressure of Cadmium and Doxycycline on the Antibiotic and Heavy Metal Resistance Genes in Ditch Wetlands

Abstract: Abuse of heavy metals and antibiotics results in the dissemination of metal resistance genes (MRGs) and antibiotic resistance genes (ARGs). Ditch wetlands are important sinks for heavy metals and antibiotics. The relationships between bacterial communities and MRG/ARG dissemination under dual stresses of heavy metals and antibiotics remain unclear. The responses of MRGs and ARGs to the co-selective pressure of cadmium (Cd) and doxycycline (DC) in ditch wetlands were investigated after 7-day and 84-day exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…carrying bla TEM , copA, copB, pcoD , and zntA . Experiments using microcosms of wetland sediments demonstrated through metagenomic qPCR that doxycycline (50 mg l −1 ) and cadmium (0.5–5 mg l −1 ) exposure for 3 months increased MRG and ARG relative abundance more than either agent on their own (Yu et al 2022 ). In this study, both agents were positively correlated with individual resistance genes and bacterial genera, with Acinetobacter being one notable predicted host for MRGs, ARGs, and integrons.…”
Section: Evidence For Co-resistancementioning
confidence: 99%
“…carrying bla TEM , copA, copB, pcoD , and zntA . Experiments using microcosms of wetland sediments demonstrated through metagenomic qPCR that doxycycline (50 mg l −1 ) and cadmium (0.5–5 mg l −1 ) exposure for 3 months increased MRG and ARG relative abundance more than either agent on their own (Yu et al 2022 ). In this study, both agents were positively correlated with individual resistance genes and bacterial genera, with Acinetobacter being one notable predicted host for MRGs, ARGs, and integrons.…”
Section: Evidence For Co-resistancementioning
confidence: 99%
“…Metal resistance determinants may be found on the chromosome or in clusters on bacterial plasmids. Sometimes these heavy metal resistance genes are found on the same plasmids as multiple antimicrobial resistance (AMR) determinants [102,103]. Efflux pumps work in conjunction with other resistance mechanisms such as genes coding for metal oxidases and often these genes are located on the same operon and are subject to the similar levels of regulation.…”
Section: Heavy Metal Resistancementioning
confidence: 99%
“…Notably, heavy metals and antibiotics can induce cross-resistance, and thus, bacteria can become resistant to both. Toxic metals are assumed to exert selective pressure on metal-resistant bacteria, and genes associated with heavy metals, such as arsenic and cadmium, are frequently found in plasmids associated with ARGs [ 12 , 13 ]. Another study found that arsenic stress increases ARG abundance and dissemination risk [ 5 ].…”
Section: Introductionmentioning
confidence: 99%